Overlaps of private sector with public sector around the globe - Kensinger, John W. (Emerald, 2015)
Contributions assess the benefits to local banks around the Bakken Formation, the effect of corporate governance on valuation in India, and the undermining of real estate investment because of regulatory uncertainties. We also have studies of dividend policy and systemic risk in emerging markets, plus improvements in quantitative methods.
Keywords: Finance -- Research.; Finance, Public.; elektronické knihy; electronic books